13CO2 labeling kinetics in maize reveal impaired efficiency of C4 photosynthesis under low irradiance. Issue 1 (25th June 2022) - Medeiros, David B; Ishihara, Hirofumi; Guenther, Manuela; Rosado de Souza, Laise; Fernie, Alisdair R; Stitt, Mark; Arrivault, Stéphanie
Abstract: C4 photosynthesis allows faster photosynthetic rates and higher water and nitrogen use efficiency than C3 photosynthesis, but at the cost of lower quantum yield due to the energy requirement of its biochemical carbon concentration mechanism. It has also been suspected that its operation may be impaired in low irradiance. To investigate fluxes under moderate and low irradiance, maize ( Zea mays ) was grown at 550 µmol photons m −2 s −l and 13 CO2 pulse-labeling was performed at growth irradiance or several hours after transfer to 160 µmol photons m −2 s −1 . Analysis by liquid chromatography/tandem mass spectrometry or gas chromatography/mass spectrometry provided information about pool size and labeling kinetics for 32 metabolites and allowed estimation of flux at many steps in C4 photosynthesis. The results highlighted several sources of inefficiency in low light. These included excess flux at phospho enol pyruvate carboxylase, restriction of decarboxylation by NADP-malic enzyme, and a shift to increased CO2 incorporation into aspartate, less effective use of metabolite pools to drive intercellular shuttles, and higher relative and absolute rates of photorespiration. The latter provides evidence for a lower bundle sheath CO2 concentration in low irradiance, implying that operation of the CO2 concentration mechanism is impaired in this condition. The analyses also revealed rapid exchange of carbon between the Calvin–Benson cycle and the CO2 -concentration shuttle, which allows rapid adjustment of the balance between CO2 concentration and assimilation, and accumulation of large amounts of photorespiratory intermediates in low light that provides a major carbon reservoir to build up C4 metabolite pools when irradiance increases. Abstract : Analysis of metabolite pools, sizes, and fluxes reveals that multiple interlocking factors decrease the efficiency of photosynthesis in low irradiance in maize.